RETRACTED: The Association of COVID-19 Pandemic Stress With Health-Related Quality of Life in the Kingdom of Saudi Arabia: A Cross-Sectional Analytical Study - Hawash, Manal Mohammed; Alhazmi, Amani Hamad; Wafik, Wagida; Muzammil, Khursheed; Mushfiq, Sakeena; Ahmed, Hala Awad (Frontiers in Public Health, 2021)
Background: There is a global disaster since WHO declared COVID-19 as a pandemic. With the increase in cases & mortality, various health issues viz., stress, mental disorders & altered Health-Related Quality of Life (HRQoL) have been observed during COVID-19 lockdowns. This study assessed the impact of COVID-19 pandemic stress on HRQoL in the Kingdom of Saudi Arabia. Methods: This cross-sectional analytical study included residents of Saudi Arabia aged 18 years and above. Convenience, snowball, non-probability sampling technique was used. A web-based, self-administered, electronic questionnaire in Arabic language having three sections; Sociodemographic & clinical profile, Standard PSS-10, and Standard SF-12 was used as the study tool and distributed through various social media means. The study period was of two months. Data were analyzed using SPSS version 25. Descriptive statistics, Pearson’s correlation coefficient, independent sample t-test and the one-way analysis of variance (ANOVA) were employed for suitable statistical analysis. Results: Nearly two-thirds of the subjects were aged between 18 to  40 years. The majority (83.0%) reported as having no chronic disease, and 69.5% had no contact history with COVID-19 cases. The Mean ± SD of Mental Component Summary (MCS) & Physical Component Summary (PCS) was 32.34 ± 25.30 & 41.65 ± 11.82 respectively. A higher proportion (67.6%) had a moderate level of COVID-19 stress. A significant negative relationship between total stress scores and HRQoL domains was observed. Conclusions: COVID-19 stress has a significant negative impact on both physical and mental HRQoL in which MCS score was significantly lower than PCS score. A holistic approach is recommended to evaluate the effectiveness of stress management programs.